The Role of Tourists' Emotional Experiences in Recommending Tourist Attractions: A Case Study of Tourist Satisfaction on Onrust Island - Toana, Rangga Dalu Aji (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Onrust Island, which is located in the Thousand Islands, is one of the islands that has a high historical value and is declared a protected historic site. Besides museums, on this island there are ruins of a fort, a windmill, cannon, some hajj quarantine building, and graves of VOC legacy. Even though the government has now opened this island as a historical tourist destination, to date, not many people are interested in visiting the island. This research is aimed at answering the questions of what causes Onrust Island to be less recommended by tourists to visit and what solutions must be taken so that Onrust Island can become a recommended tourist destination based on tourist emotional experience. This is a qualitative research with a case study approach. Data collection used semi-structured interviews with 5 domestic travelers and 5 foreign travelers. The aim is to see if there are differences of opinions between domestic travelers and foreign travelers about Onrust Island. The results of this study indicate that the dimensions of tourism product quality consisting of attractions of objects, information, public facilities, human resources, services, cleanliness and accessibility greatly determine the satisfaction or dissatisfaction of tourists. This study also proves that tourists who visit Onrust Island still found a negative emotional experience that is related to dissatisfaction which will result in unwillingness to make recommendations to visit the island.